Knowledge Management and Role of ICT for Development - , Sarita Upadhyay, Raj Boria, Ajit Prajapati (International Journal of Scientific Research and Management (IJSRM), 2017)
Knowledge Management has become the key factor for the success of all organization. KM is all aboutmaking available the right knowledge to the right people. It is about making sure that an organization can learn, andthat it will be able to retrieve and use its knowledge assets in current applications as they are needed. Most often,generating value from such assets involves sharing them among employees, departments and even with othercompanies or institutes in an effort to devise best practices. Knowledge management is the practice of identifying,creating, communicating, socializing, measuring and improving knowledge to support strategic objectives. (Anna Mar,Simplicable). Thus, Knowledge sharing is facilitate through information and communication technologies includingcomputers, telephones, databases, e-mail, data mining system, video conferencing equipment, search engine and manymore. This paper focus on identify the significant role of information and communication technology in knowledgemanagement.